2013
DOI: 10.1002/jcop.21563
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of the Ethnic Density Effect: Issues of Acculturation, Discrimination and Social Support

Abstract: Ecological factors in psychological acculturation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 47 publications
5
61
0
1
Order By: Relevance
“…Several theories have been proposed to explain this phenomenon including lower social support for black patients living in wealthier, commonly white, neighborhoods and greater racial discrimination in high SES neighborhoods. 43,44 Our study has important implications for efforts to understand and eliminate socioeconomic disparities in pediatric cardiac outcomes. Given the strong, inverse relationship between neighborhood SES and mortality after the Norwood procedure, postoperative care should focus not only on operative management strategies but also socioeconomic and environmental factors, which may be equally important determinants of patient outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Several theories have been proposed to explain this phenomenon including lower social support for black patients living in wealthier, commonly white, neighborhoods and greater racial discrimination in high SES neighborhoods. 43,44 Our study has important implications for efforts to understand and eliminate socioeconomic disparities in pediatric cardiac outcomes. Given the strong, inverse relationship between neighborhood SES and mortality after the Norwood procedure, postoperative care should focus not only on operative management strategies but also socioeconomic and environmental factors, which may be equally important determinants of patient outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…23 This support may be particularly important in the setting of AMI when learning how to manage their condition or requiring assistance with activities of daily living. In addition, blacks living in high-income white neighborhoods may experience greater discrimination than those living in black neighborhoods, 23,24 which can, in turn, adversely affect physical and mental health. 25,26 Racial discrimination, whether perceived or actual, has been shown to increase cardiovascular disease risk and negatively impact health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted in London (Whitley, Prince, McKenzie, & Stewart, 2006) suggested that social networks, culturally-specific services and facilities, and reduced everyday racism may help to explain the mechanisms underlying the relationship of ethnic density with mental health for ethnic minorities. Using a diverse sample of immigrant students in Montreal, Canada, Jurcik et al (2013) tested the mediating roles of discrimination and social support and found that the negative relation between perceived ethnic density and depression is mediated by discrimination but not by social support. These equivocal findings suggest that the mechanisms linking ethnic density to mental health are likely heterogeneous and operate in complex ways among different racial and ethnic groups and across national contexts.…”
Section: Introductionmentioning
confidence: 99%